Studi Cross Sectional Komunikasi Orang Tua Membentuk Perilaku Seksual Remaja : Cross Sectional Study of Parental Communication Shaping Sexual Behavior Adolescents - Agus Sri Banowo; Haristio Maulana (NERS Jurnal Keperawatan, 2021)
Adolescent is a phase or stage where there is sicnificant developmental transition with many bewilderment and hesitation. Adolescent was in critical period of sexual development where they will experienced emotional dan social development, such as attraction to the opposite sex and dating. Open minded and comfort communication between adolescent and parent about sexuality will decrease negative risks of risky sexual behavior. This study aims was to determine the relationship between parental communication and risky sexual behavior in adolescent. This study was a quantitative study using correlative descriptive method with cross sectional design. This study used the SCS (Sexual Communication Scale) questionnaire. The results of the chi square statistical analysis showed significant value of p = 0.000 (p <0.05), it was concluded that there was a significant relationship between communication between parents and adolescents with risky sexual behavior. These study suggested nurses with a family nursing care approach have to begin improving appropriate parental communication in facilitating care of adolescent in order to control expected sexual behavior.